Analisis Penurunan Kadar Zn(II) pada Biosorpsi Limbah Cair Artifisial Menggunakan Mikroalga Tetraselmis chuii dengan Pengaruh Konsentrasi dan Warna Cahaya - Dzulfikar, Muhamad Hanif; Putri, Desita Ramadona Syah; Gunawan, Karina Larasati; Prianto, Haekal Irfan Titan; Firnandi, Rahmad; Dewi, Tanti Utami (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2023)
Zn(II) is one of the heavy metals whose presence in large quantities can cause toxicity in water bodies so that it can cause death to organisms in the waters. The purpose of this study was to analyze the effect of red light color, contact time, and concentration on reducing Zn(II) levels in artificial wastewater using Tetraselmis chuii microalgae. The color of light applied was red with a wavelength of 620 – 760 nm. While the contact time varied was 30 minutes, 45 minutes, and 60 minutes with a concentration variation of 5 mg/L and 15 mg/L. The analysis conducted to identify the reduction of Zn(II) using Tetraselmis chuii microalgae is UV-Vis spectrophotometer analysis. The best Zn(II) removal efficiency was shown in the variation of contact time of 60 minutes, and initial concentration of 5 mg/L of 51.0805%.